Reinstatement of National Guidelines of State Policy Within Indonesian Presidential System: The Possibility - Muhtadi Muhtadi; Zulkarnain Ridlwan (Universitas Lampung, 2023)
Placing the National Guidelines of State Policy (GBHN or PPHN) made by the People's Consultative Assembly (MPR) as a guideline for the President can potentially reposition MPR above the President. Such an idea of a state has been implemented in Indonesia for no less than 54 years (1945-1999). This paper aims to analyze the basic characteristics of the presidential system and assess the compatibility of PPHN with the presidential system, with the novelty which then offers a model for pouring PPHN into laws and regulations that align with Indonesia's presidential system. Based on the conceptual and theoretical approaches, it can be concluded: First, the basic character of a presidential system is to separate the legislature from the executive, so no accountability mechanism puts the President down as subordinate to the legislature. PPHN implementation can shift this separation towards an accountability model, a feature of a parliamentary system. Second, PPHN can be re-enforced in a presidential system, with the prerequisite that no accountability mechanism puts the President under MPR. Third, pouring PPHN into the form of a Law replacing the RPJPN Law will be more relevant to avoid a government system shifting. However, providing a checks and balances mechanism for the President through the House of Representatives' budgetary rights is still necessary.